EVALUASI IMPLEMENTASI SISTEM PENGENDALIAN INTERNAL PADA PROSES PENETAPAN DAN PEMBERIAN HARGA (STUDI PADA DIREKTORAT KARGO PT GARUDA INDONESIA (PERSERO) TBK) - SALSABILA, SYIFA FADHIYAH (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims at evaluating the effectiveness of the implementation of internal control system in price determination process applied by the Directorate of Cargo of PT Garuda Indonesia (Persero) Tbk. This qualitative descriptive research applies a case â€“ study approach. The data are collected through interview, observation, and document study, completed by secondary data obtained from various sources. The result of the effectiveness measurement shows a figure of 94%, meaning that the internal control system in price determination process is classified â€œeffectiveâ€ and it has run well in accordance with Committee of theSponsoring Organization (COSO) internal control system components. Some improvements, however, are still needed to improve the effectiveness level.Keywords: Internal Control System, Price Determination Process, Effectivity, COSO